Melodic Characteristics of Oud Instrument Compositions with the Iraqi Symphony Orchestra (Saleem Salim) A Model: رعد عدنان علوان (Al-Academy, 2019)
The variety of ideas and freedom of expression among the authors who are looking for everything new that serves the goals of musical and aesthetic expression, which calls for the use of traditional musical instruments with the great composition of musical instruments known as the orchestra represents a great challenge in several aspects. The incompetence of some of these instruments or limited capabilities or its costly method of performance sometimes forbids its use permanently in this great composition. It was necessary to have some problems facing the composer and the player on the one hand and the recipient on the other hand, who must be looking for perfection. Among those instruments that are used regularly in the works of the orchestra are the traditional Oud instruments or what we call popular instruments. (What are the melodic characteristics of the Oud instrument in the works of Saleem Salim for the Iraqi Symphony Orchestra?). The researcher, in the theoretical framework, addressed the melodic characteristics of the Oud instrument and the melodic construction in the compositions of the Iraqi symphony orchestra. The research procedures included a melody analysis by Saleem Salem. The researcher came up with the following conclusion: Many different types of quartet species appeared in the sample. This indicates the melodic richness and the diversity of the maqam transitions. It also means that the melody did not depart the oriental Arabic maqam environment, although the work is written for the Oud instrument with the accompaniment of the orchestra